Studi Komparasi Terhadap Resiliensi Siswa Berdasarkan Gender - Muwakhidah, Muwakhidah; Lianawati, Ayong; Puspitasari, Yuanita (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
Resilience is an individual's quality to rise and adapt to social change. Gender is one of the inconsistent resilience factors, so it needs to be tested. This study aims to prove the difference in resilience between male studens with female students. The research method used a comparative study of 188 male students and 188 female students from SMA, SMK, or MA in the city of Surabaya. The results of the ANOVA test showed that there was a significant difference between male and female resilience. Descriptive test shows women are superior in resilience scores than men. How to resolve and deal with change is the main indicator that makes the two groups have different resilience